HUBUNGAN SIKAP KARYAWAN DENGAN MOTIVASI KERJA DAN PRESTASI KERJA - I Made Widyasari (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2013)
The purpose of the research is to find the relationship of employee on performance indicators to the needs of society’s demands for high-quality services. The use of performance towards work motivationand work performance. Populations of the study are 50 employees at housekeeping department at some small hotels and villa located in Sanur and Kuta. Data obtained from the questionnaire and analysismethodology is using Partial Least Squares (PLS). The results showed that employee attitude on performance indicator insignificant related to employee motivation and to work performance, work motivation is related negatively on work performance. The company should use timing of the work speed in process of performance appraisal, and the next researcher is advised to extend the number of samples to several categories of hotels.